2020
DOI: 10.3310/hta24710
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatments compared with early structured physiotherapy in secondary care for adults with primary frozen shoulder: the UK FROST three-arm RCT

Abstract: Background Frozen shoulder causes pain and stiffness. It affects around 10% of people in their fifties and is slightly more common in women. Costly and invasive surgical interventions are used, without high-quality evidence that these are effective. Objectives To compare the clinical effectiveness and cost-effectiveness of three treatments in secondary care for adults with frozen shoulder; to qualitatively explore the accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 118 publications
(194 reference statements)
2
3
0
4
Order By: Relevance
“…In a recent study that compared the clinical and cost effectiveness of three interventions for adults with frozen shoulder (early structured physiotherapy with a steroid injection, manipulation under anesthesia with a steroid injection followed by postprocedural physiotherapy, and arthroscopic capsular release followed by manipulation and post-procedural physiotherapy) [9], the authors reported that no conclusions regarding the superiority of one intervention over another could be drawn. While physiotherapy with a steroid injection is the most accessible option, manipulation under anesthesia is the most cost-effective option, compared to early structured physiotherapy or arthroscopic capsular release [9]. For all interventions, the main anticipated outcomes are increased ROM and reduced pain levels.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study that compared the clinical and cost effectiveness of three interventions for adults with frozen shoulder (early structured physiotherapy with a steroid injection, manipulation under anesthesia with a steroid injection followed by postprocedural physiotherapy, and arthroscopic capsular release followed by manipulation and post-procedural physiotherapy) [9], the authors reported that no conclusions regarding the superiority of one intervention over another could be drawn. While physiotherapy with a steroid injection is the most accessible option, manipulation under anesthesia is the most cost-effective option, compared to early structured physiotherapy or arthroscopic capsular release [9]. For all interventions, the main anticipated outcomes are increased ROM and reduced pain levels.…”
Section: Introductionmentioning
confidence: 99%
“…Актуальними є результати нещодавнього великого дослідження з оцінки клінічної та економічної ефективності двох інвазивних і дорогих хірургічних втручань (МПА, АКВ) та ранньої структурованої ФТ [28,29,30]. Рання структурована ФТ включала методи мобілізації та структуровану домашню програму вправ.…”
unclassified
“…Щодо результатів, то усі середні відмінності між групами в оцінці болю і функції плеча через 12 місяців від початку лікування були меншими, ніж цільові відмінності. Усі методи призвели до значного покращення болю та функції плеча [29,30].…”
unclassified
See 2 more Smart Citations